Current application of polymers and nano materials : special topic volume with invited peer reviewed papers only (Materials science forum, 2010)
This Special Topic Volume constitutes the contributions of thirty-nine experts from the international scientific community who are involved in this field of research. It covers thoroughly some of the latest applications of polymers and nano-materials to solar-cells, fuel cells, catalysis, coatings, ion-exchange and sensors. It presents an up-to-date and in-depth coverage of the chemistry, physics, materials science and engineering applications of polymers and nano-materials. This remarkable cooperation of distinguished experts has resulted in a comprehensive review of the subject.